Exploring birth advantages in Italian swimming. How cultural and contextual features of the environment shape male youth Italian swimmers developmental experiences and progression within the model - Morganti, G.; Vitarelli, M.; Strassoldo di Villanova, F.; Ruscello, B.; Padua, E. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Introduction The Standard Model of Talent Development (SMTD) is a common deterministic talent pathway adopted by sports systems. Athletes` progression through the SMTD is related to acquiring early abilities and achieving early results. The SMTD causes the specialization of the selected few and the de-selection of the many unable to fit in with the requirements of the organizations and leads to several reported selection biases [1]. Youth performance outcomes are dependent on contextual factors, which eventually lead to birth advantages (relative age effects (RAEs) and birthplace effects). This study aimed to investigate birth advantages` influences on the Italian swimming talent pathway. We hypothesized that (a) value-directedness towards competition and working hard promoted in Italian swimming, reflected in early specialization practices and early success promotion, would cause the presence of RAEs; and (b) regional disparities that characterize Italy, would define swimmers` developmental experiences and their skill-acquisition processes. Methods We explored the birth quarter (BQ) and place of early development (PED) of male Italian youth swimmers (age groups: 15-year, n=341, 17-year, n=380), competing at the annual Winter Italian National Youth Championship. To explore whether birth advantages influence national-level youth swimmers` participation, the observed BQs and PEDs distribution of the 15-year age group were compared to the expected values (i.e., census statistics). Moreover, to investigate how birth advantages influence swimmers` ability to maintain their national status, the observed BQs and PEDs distributions of the 17-year age group were compared to the expected values (i.e., 15-year age group). Results Results revealed skewed BQs (P